Therapeutic advances and future directions in Helicobacter pylori eradication - Suresh, Vidya; Sreekumar, Amritavarshini; Kumar, Anil; Sadasivan, Shine; Biswas, Raja; Biswas, Lalitha (Frontiers in Microbiology, 2025)
Helicobacter pylori (H. pylori) is a globally prevalent pathogen associated with a spectrum of gastrointestinal diseases, including chronic gastritis, peptic ulcer disease, and gastric malignancies. Although clarithromycin-based triple therapy continues to be effective in certain geographic areas, increasing global resistance highlights the need for treatment approaches tailored to local antibiotic susceptibility patterns. Recent clinical trials have shifted toward optimized quadruple regimens, particularly bismuth- and vonoprazan-based therapies, and resistance-guided treatment. Novel agents such as Rifasutenizol (TNP-2198) are entering phase 3 evaluation and show activity against multidrug-resistant strains. Adjunctive and alternative strategies including probiotics, phytochemicals, phage-derived enzymes, and nanoparticle-based delivery demonstrate synergistic effects in improving eradication and reducing antibiotic-associated adverse events. Multi-strain probiotic formulations and plant-derived compounds such as curcumin, catechins, and quercetin consistently suppress H. pylori virulence pathways and gastric inflammation in clinical and preclinical studies. This review provides an overview of current evidence from clinical trials and emerging therapeutic innovations, emphasizing balanced integration of conventional and next-generation approaches for sustainable global H. pylori management.